(untitled) (Research, Society and Development, 2020)
The Amazon river prawn Macrobrachium amazonicum is a fishing resource exploited for subsistence and commercial purposes in the Pará State, being consumed by members of all social classes. The objective of this study was to analyze the consumer profile of Amazon river prawn in the Pará State. In the period from February to August 2019, a total of 1,260 were administered to fish consumers in the municipalities of Belém, Cametá, Tucuruí, Santarém, Altamira and Breves. Socioeconomic and consumption information were tabulated on spreadsheets and presented using descriptive statistics. It was found that 92.3% of the public addressed consumed the crustacean and that 82% of this total had a monthly family income of up to two minimum wages. Regarding the frequency, 37.2% reported consuming the product at least once a week. The consumption preference of 71.7% was for whole shrimp and 54.2% prioritized the purchase of live or fresh product. The low exigency of most consumers in terms of presentation and conservation the product is mainly due to the low purchasing power and the culture of purchasing foodstuffs in public spaces.